Using radio frequency identification technology in distribution management: a case study on third-party logistics. (1st December 2006) - Choy, K.L.; Lau, Henry C.W.; Kwok, S.K.; So, Stuart C.K.; Chow, K.H.; Lee, W.B.
In the past two decades, the highly competitive marketplace forces many manufacturing firms in Hong Kong moving their production lines to the Pearl River Delta (PRD) region where the labour cost is low. The changes not only bring ample business opportunity to these firms, but also trigger a structural transformation in distribution logistics. Therefore, new methods are required for local logistics service providers to cope with these changes. In this study, a logistics information system called Integrated Logistics Information Management System (ILIMS) is proposed to simplify the distribution process with the help of Radio Frequency Identification (RFID) technology. A case study is discussed in applying ILIMS to solve distribution management problems of International Logistics Solutions Limited (ILSL), a medium-sized logistics service company operating in Hong Kong and the PRD region. By using this RFID-enabled system, the overall distribution performance of the company is greatly improved.